Identifikasi Kandungan Karbon dan Nitrogen pada Kotoran Sapi Feedlot Polije dan Kulit Pisang - Saiful Anwar; Nur Faizin; Zeni Ulma; Risse Entikaria Rachmanita; Michael Joko Wibowo (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
Politeknik Negeri Jember has cow dung waste which needs to be utilized so that it does not pollute the environment. However, the C/N ratio of cow dung is 24. To optimize biogas production, raw materials that contain high carbon sources can be added. Banana peel is waste with a carbon content of 36%, so it is an alternative raw material that can be used to produce biogas. Analysis of total C from cow dung and banana peels was carried out using spectrophotometric methods. Total N analysis of cow feces and banana peels was carried out based on the Kjeldhal method. The sample weight for each type of material was made of 2 samples, for banana peel the weight of the samples made was 236 mg and 312 mg. Meanwhile, for cow feces, the sample weights were 223 mg and 291 mg. The average organic carbon obtained from banana peels is 2.413%, while the organic carbon in cow feces is 4.569%. This result was obtained by comparing the relationship between the sample's absolute standard and concentration against a graph. In the process of making biogas, the nitrogen content should not be excessive because this can result in the production of excess ammonia gas rather than methane gas. The average nitrogen content in banana peels and cow feces is 0.062% and 0.160% respectively. These results indicate that the nitrogen content in the sample is relatively very small so it has the potential to be used as a raw material for making biogas. The results of the organic carbon and nitrogen content in banana peels and cow dung were compared. The average value of the C/N ratio of banana peel is 39.158% and cow feces is 28.707%. These two results indicate that both samples have the potential to produce good biogas.